Physicochemical and sensory characteristics of sweet potato chips undergoing different cooking methods - Caetano, Priscilla Kárim; Mariano-nasser, Flávia Aparecida De Carvalho; MendonÇa, Veridiana Zocoler De; Furlaneto, Karina Aparecida; Daiuto, Erica Regina; Vieites, Rogério Lopes (Sociedade Brasileira de Ciência e Tecnologia de Alimentos, 2017)
Abstract The current study aimed to evaluate the feasibility and acceptability of sweet potato chips from three cultivars undergoing different cooking methods. The sweet potatoes used were cream peel with yellow-flesh, pink peel with yellow-flesh and white peel with white-flesh. Fresh tubers were characterized in terms of centesimal composition and the following contents: soluble solids, pH, titratable acidity, reducing sugar, total sugar, starch and colour. Chips were deep-fried with canola oil, commercial oven-baked and air fried. Therefore, the three sweet potato cultivars did not differ statistically in terms of reducing sugars; however, TB presented the lowest starch content. The centesimal composition was accordingly the literature whose differences referred to the type of cultivar. Oven-baked and air fried chips presented the lowest fat and moisture content, which increased their shelf life. Furthermore, all deep-fried sweet potato chips showed the best sensory acceptance and purchase intent by tasters.
Keywords: Ipomoea batatas L.; processing; acceptability; oil free fryer, frying